Dosimetric Evaluation of Volumetric Modulated Arc Therapy (VMAT) and Intensity Modulated Radiotherapy (IMRT) Using AAPM TG 119 Protocol - Nainggolan A.; Pawiro S. A. (Journal of Biomedical Physics and Engineering, 2019)
Background: The commissioning accuracy of Volumetric Modulated Arc Therapy (VMAT) need to be evaluated. Objective: To test and evaluate commissioning accuracy of VMAT based on the TG 119 protocols at local institution. Material and Methods: The phantom, structure sets, VMAT and IMRT beam parameter setup, dose prescriptions and planning objectives were following TG 119 guidelines to create local treatment plans of VMAT and IMRT. The local planning results were compared with the results of TG 119. Point measurement at high and low dose regions were measured using three ionization chambers with different active volumes (CC01, CC13, FC65G). The composite dose was measured by a 2D detector array and analyzed for the percentage of points passing the gamma criteria of 3 % dose difference (DD) and 3 mm distance-to-agreement (DTA) and 2 % DD and 2 mm DTA. Results: The local treatment plans of VMAT and IMRT capable to meet the dose goals criteria set by TG 119 except for C-shape hard. Three ionization chambers with various active volumes for point measurement showed an increase in the confidence limit (CL), the larger the active volume was found proportional to increase the value of CL. The results obtained from ion chambers CC01 and CC13 could met the dose criteria set by TG 119, but results obtained from ion chamber FC65G fail the criteria. All gamma evaluation results show more than 95% data points pass the criteria of 3% DD and 3 mm DTA and the gamma index CL results fall within the TG 119 criteria, which is below 12.4. Conclusion: TG 119 methodology and recommendations have successfully been used to evaluate commissioning accuracy of VMAT. The CL value of the study could be used as a reference and recommendation to evaluate the accuracy and integrity of treatment planning and treatment delivery systems of VMAT and IMRT. Citation: Nainggolan A, Pawiro S. A. Dosimetric Evaluation of Volumetric Modulated Arc Therapy (VMAT) and Intensity Modulated Radiotherapy (IMRT) Using AAPM TG 119 Protocol. J Biomed Phys Eng. 2019;9(4):395-408. https://doi.org/10.31661/jbpe.v0i0.839.